2015
DOI: 10.1007/s11745-015-4010-3
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Wax Ester Content and Composition in Euglena gracilis with Gene Silencing of 3‐ketoacyl‐CoA Thiolase Isozymes

Abstract: Euglena gracilis produces wax ester under hypoxic and anaerobic culture conditions with a net synthesis of ATP. In wax ester fermentation, fatty acids are synthesized by reversing beta-oxidation in mitochondria. A major species of wax ester produced by E. gracilis is myristyl myristate (14:0-14:0Alc). Because of its shorter carbon chain length with saturated compounds, biodiesel produced from E. gracilis wax ester may have good cold flow properties with high oxidative stability. We reasoned that a slight metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 31 publications
0
32
0
Order By: Relevance
“…C28 wax esters were dominant in the control cells and in thiolase-silenced cells C26 (isoform 1) and C27 (isoform 2). Gene silencing of these two isoforms significantly increased the amount and the ratio of wax esters with an acyl chain length shorter than C26 (Nakazawa et al 2015). The study suggests different roles for each isoenzyme in hypoxic wax ester production (Nakazawa et al 2015).…”
Section: Five Different Systems For Fatty Acid Synthesismentioning
confidence: 77%
See 2 more Smart Citations
“…C28 wax esters were dominant in the control cells and in thiolase-silenced cells C26 (isoform 1) and C27 (isoform 2). Gene silencing of these two isoforms significantly increased the amount and the ratio of wax esters with an acyl chain length shorter than C26 (Nakazawa et al 2015). The study suggests different roles for each isoenzyme in hypoxic wax ester production (Nakazawa et al 2015).…”
Section: Five Different Systems For Fatty Acid Synthesismentioning
confidence: 77%
“…A recent study showed that gene silencing of this enzyme altered both the wax ester content and the wax ester composition in E. gracilis, inducing a significant compositional shift to shorter carbon chain lengths in wax esters (Nakazawa et al 2015). Six putative 3-ketoacyl-CoA thiolase isoenzymes were found in an E. gracilis EST database (O'Brien et al 2007), but only the gene silencing of three of them had an effect on wax esters.…”
Section: Five Different Systems For Fatty Acid Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…This isozyme was highly active with both crotonyl-CoA and trans-2-hexenoyl-CoA (C 6 ), and both NADH and NADPH were suitable electron donors. In addition to TER, 3-ketoacylCoA thiolase isozymes that catalyze the condensation reaction of acyl-CoA and acetyl-CoA in the mitochondrial fatty acid synthesis, have been studied in Euglena (Nakazawa et al 2015) (for details, see Sect. 13.4.3).…”
Section: Mitochondrial Fatty Acid Synthetic Systemmentioning
confidence: 99%
“…A likely strategic point for increased production of wax esters in Euglena is thus elevating the TER activity by genetic engineering. Nakazawa et al (2015) reported that at least three isozymes of 3-ketoacyl-CoA thiolase (EgKAT1-3) participated in mitochondrial fatty acid synthesis in the wax ester fermentation. It was also shown that silencing of EgKAT3 led to a decreased wax ester content while silencing of EgKAT1 and EgKAT2 led to a significant shift to shorter carbon chain lengths in the wax esters.…”
Section: Genetic Engineering Of the Metabolic Pathways From Paramylonmentioning
confidence: 99%